A heterotrophic nitrification - Aerobic denitrification bacterium - HU, QINGPING; HE, FENG; WEN, CAIFANG (The Indian Journal of Agricultural Sciences, 2018)
A bacterial strain named Pseudomonas stutzeri ZH-1, which exhibits the ability of efficient heterotrophic nitrification and aerobic denitrification, was isolated from 20 bacterial strains in the sludge of Fenhe River (in Shanxi Province, China) and identified by 16S-rDNA sequencing as a strain of Pseudomonas stutzeri. The cells of strain ZH-1 were Gram-negative, non-motile and short rod-shaped. In order to further understand its removal ability, several experiments were conducted to identify the growth and nitrogen removal response at different factors. The results showed that the optimum conditions is sodium citrate as carbon source, C/N 12, shaking speed >200 rpm, pH 9, temperature 25-35Â°C and nitrogen concentration >150mg/L. The average removal rate for NH4+ -N, NO3 - -N, NO2 - -N can be as high as 4.27, 5.53 and 4.30 mg/L/h for synthetic wastewater, respectively. In particular, the strain ZH-1 showed an amazing ability of rapid degradation for NH4 + -N , NO3 - -N and NO2 - -N under aerobic conditions and it might be a suitable candidate to simultaneously aerobic nitrification/denitrification for future full-scale applications in wastewater treatment.